Impact of farmer field schools on agricultural productivity and poverty in East Africa - Davis, Kristin E.; Nkonya, Ephraim M.; Kato, Edward; Mekonnen, Daniel Ayalew; Odendo, Martins; Miiro, Richard; Nkuba, Jackson (International Food Policy Research Institute, 2010)
Farmer field schools (FFSs) are a popular education and extension approach worldwide. Such schools use experiential learning and a group approach to facilitate farmers in making decisions, solving problems, and learning new techniques. However, there is limited or conflicting evidence as to their effect on productivity and poverty, especially in East Africa. This study is unique in that it uses a longitudinal impact evaluation (difference in difference approach) with quasi-experimental methods (propensity score matching and covariate matching) together with qualitative approaches to provide rigorous evidence to policymakers and other stakeholders on an FFS project in Kenya, Tanzania, and Uganda. The study provides evidence on participation in FFSs and on the effects of FFSs on various outcomes.